Identification and Quantification of Microplastics in Aquaculture Environment - Xiang, Shuo; Xie, Yuqun; Sun, Xuemei; Du, Hao; Wang, Jun (Frontiers in Marine Science, 2022)
The existence of microplastics (MPs) poses a potential threat to the entire ecosystem and has gained wide public attention. As an essential source of aquatic products, aquaculture industries are inevitably subjected to the pollution of MPs, particularly when the plastic products are widely used in aquaculture. Even so, the identification of MPs in aquaculture is rarely reported. Hence, high-efficient analytical methods for accurate detection of MPs in the aquaculture environment are of utmost significance. This review comprehensively summarizes the analytical methods for MPs in aquaculture, including sampling, extraction, and qualitative and quantitative analyses of MPs. MPs are identified and quantified mainly by visual inspection, spectroscopy, or thermal analysis. In addition, this review also points out the limitations of these methods and the accuracy of quality control. Finally, the need for establishing standard methods is emphasized, and suggestions for future research are also proposed.